The relationship between muscle deoxygenation and activation in different muscles of the quadriceps during cycle ramp exercise - Chin, L. M. K.; Kowalchuk, J. M.; Barstow, T. J.; Kondo, N.; Amano, T.; Shiojiri, T.; Koga, S. (Journal of Applied Physiology, 2011)
The relationship between muscle deoxygenation and activation was examined in three different muscles of the quadriceps during cycling ramp exercise. Seven young male adults (24 ± 3 yr; mean ± SD) pedaled at 60 rpm to exhaustion, with a work rate (WR) increase of 20 W/min. Pulmonary oxygen uptake was measured breath-by-breath, while muscle deoxygenation (HHb) and activity were measured by time-resolved near-infrared spectroscopy (NIRS) and surface electromyography (EMG), respectively, at the vastus lateralis (VL), rectus femoris (RF), and vastus medialis (VM). Muscle deoxygenation was corrected for adipose tissue thickness and normalized to the amplitude of the HHb response, while EMG signals were integrated (iEMG) and normalized to the maximum iEMG determined from maximal voluntary contractions. Muscle deoxygenation and activation were then plotted as a percentage of maximal work rate (%WRmax). The HHb response for all three muscle groups was fitted by a sigmoid function, which was determined as the best fitting model. The c/d parameter for the sigmoid fit (representing the %WRmax at 50% of the total amplitude of the HHb response) was similar between VL (47 ± 12% WRmax) and VM (43 ± 11% WRmax), yet greater (P < 0.05) for RF (65± 13% WRmax), demonstrating a "right shift" of the HHb response compared with VL and VM. The iEMG also showed that muscle activation of the RF muscle was lower (P < 0.05) compared with VL and VM throughout the majority of the ramp exercise, which may explain the different HHb response in RF. Therefore, these data suggest that the sigmoid function can be used to model the HHb response in different muscles of the quadriceps; however, simultaneous measures of muscle activation are also needed for the HHb response to be properly interpreted during cycle ramp exercise.